Temperature requirements of Colletotrichum spp. belonging to different clades - Salotti, Irene; Ji, Tao; Rossi, Vittorio (Frontiers in Plant Science, 2022)
The fungal genus Colletotrichum includes plant pathogens that cause substantial economic damage to horticultural, ornamental, and fruit tree crops worldwide. Here, we conducted a systematic literature review to retrieve and analyze the metadata on the influence of temperature on four biological processes: i) mycelial growth, ii) conidial germination, iii) infection by conidia, and iv) sporulation. The literature review considered 118 papers (selected from a total of 1641 papers found with the literature search), 19 Colletotrichum species belonging to 8 clades (acutatum, graminicola, destructivum, coccodes, dematium, gloeosporioides, and orbiculare), and 27 host plants (alfalfa, almond, apple, azalea, banana, barley, bathurst burr, blueberry, celery, chilli, coffee, corn, cotton, cowpea, grape, guava, jointvetch, lentil, lupin, olive, onion, snap bean, spinach, strawberry, tomato, watermelon, and white bean). We used the metadata to develop temperature-dependent equations representing the effect of temperature on the biological processes for the different clades and species. Inter- and intra-clades similarities and differences are analysed and discussed. A multi-factor cluster analysis identified 4 groups of clades with similar temperature dependencies. The results should facilitate further research on the biology and epidemiology of Colletotrichum species and should also contribute to the development of models for the management of anthracnose diseases.